Assistive products and the Sustainable Development Goals (SDGs). Issue 1 (December 2016) - Tebbutt, Emma; Brodmann, Rebecca; Borg, Johan; MacLachlan, Malcolm; Khasnabis, Chapal; Horvath, Robert
Abstract The Sustainable Development Goals (SDGs) have placed great emphasis on the need for much greater social inclusion, and on making deliberate efforts to reach marginalized groups. People with disabilities are often marginalized through their lack of access to a range of services and opportunities. Assistive products can help people overcome impairments and barriers enabling them to be active, participating and productive members of society. Assistive products are vital for people with disabilities, frailty and chronic illnesses; and for those with mental health problems, and gradual cognitive and physical decline characteristic of aging populations. This paper illustrates how the achievement of each of the 17 SDGs can be facilitated by the use of assistive products. Without promoting the availability of assistive products the SDGs cannot be achieved equitably. We highlight how assistive products can be considered as both a mediator and a moderator of SDG achievement. We also briefly describe how the Global Cooperation on Assistive Technology (GATE) is working to promote greater access to assistive products on a global scale.